TLE book 2 : for life long learning - Raichandani-Mansukhani, Roshi (Makati City. Diwa Learning Systems.)
TLE for lifelong learning book 2. as part of its goal of strengthening the k-12 curriculum, the Department of Education (DEPED) saw the need to equip you, high school students, with the right skills for employment. This aim eventually led to the formation of the Technology and Livelihood Education (TLE) and Technical-Vocational-Livehood (TVL) Track in the K to 12 program. This track offers different specializations and explanatory subject that you can choose from. As early as grade 7, you will already get a concreate idea on what it is like to join the workforce.
Includes index and bibliography
English text.